2022
DOI: 10.3389/fimmu.2022.1001727
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment with anti-α4β7 antibody facilitates increased gut macrophage maturity in SIV-infected rhesus macaques

Abstract: Despite advances in combination antiretroviral therapy (cART), people living with HIV (PLWH) continue to experience gastrointestinal dysfunction. Infusions of anti-α4β7 monoclonal antibodies (mAbs) have been proposed to increase virologic control during simian immunodeficiency virus (SIV) infection in macaques with mixed results. Recent evidences suggested that therapeutic efficacy of vedolizumab (a humanized anti-α4β7 mAb), during inflammatory bowel diseases depends on microbiome composition, myeloid cell dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 68 publications
4
13
1
Order By: Relevance
“…This study was planned, conducted, and reported here following the Animal Research: Reporting In Vivo Experiments (ARRIVE) guidelines. Ethical approval was obtained from the UNMC Institutional Animal Care and Use Committee (IACUC) and Institutional Biosafety Committee (IBC) for “Gut Trafficking Cells in SIV Infection” (Protocol #15-102-12) prior to initiation of the study as reported previously [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study was planned, conducted, and reported here following the Animal Research: Reporting In Vivo Experiments (ARRIVE) guidelines. Ethical approval was obtained from the UNMC Institutional Animal Care and Use Committee (IACUC) and Institutional Biosafety Committee (IBC) for “Gut Trafficking Cells in SIV Infection” (Protocol #15-102-12) prior to initiation of the study as reported previously [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Eight mAb infusions were administered regularly until week 23 (every three weeks). The protocol is shown in Figure 1(a) and was reported previously [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a clinical trial investigating anti-α4β7 monoclonal antibody therapy in PWH did not show positive effects on viral rebound upon ART interruption [58]. Moreover, in SIV-infected macaques, this therapy increased expression of CD206 and CD163 on mature duodenal macrophages, which correlated with higher viral loads [59].…”
Section: Gastrointestinal Tractmentioning
confidence: 96%